Adoption based on socio-affectiveness not subject to age limits - Sonia Seba (Oñati Socio-Legal Series)
From a critical socio-legal and comparative law position, based on the Argentine experience, it is proposed to show how adoption based on socio-affectivity is not subject to age limits, but what prevails is respect for the right to family life, coexistence or everyday life and affection. In this study, following the guidelines of the uniqueness with which cases must be addressed, some examples from Argentine jurisprudence are shared in which adoptions involving persons of legal age have been resolved, based on socio-affectiveness. The sanction of the Civil and Commercial Code of Argentina, in 2014, marks an advance in socio-affectiveness in family relationships, as well as in the resolution of cases with tailored sentences, informal judicial activity, interdisciplinary and specialty.